Knowledge States Of Primary Pupils On The Topic Of Time Involving Dates - Tan, Phei Ling (2017)
Knowledge state is a state of knowledge, specifying pupils’ level of mastery and informing their strengths and weaknesses in the tested domain. This study has three objectives: (1) to identify knowledge states of primary pupils in the topic of “Time” involving dates; (2) to compare the knowledge states of primary pupils across the three types of primary schools; and (3) to identify the types of errors made by pupils diagnosed with the most common knowledge state of each cognitive model. Survey research design was used in this study to gauge the knowledge states of the pupils. The instrument used in this study was a Cognitive Diagnostic Assessment (CDA) which measured four concepts: (1) concept of ‘after’; (2) concept of ‘before’; (3) duration of two inclusive dates; and (4) leap year.